Nauczanie społeczne Benedykta XVI wobec współczesnych problemów globalnych - Hordecki, Bartosz (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2010)
On June 29, 2009 the Encyclical Caritas in veritate (Charity in Truth) of Benedict XVI was published, where the Pope presents his social teaching. He expresses his critical diagnosis of modern societies, indicating that it is selfishness resulting from lack of faith that is the source of all social evil. Benedict XVI calls for an effort to improve the world by multiplying the acts based on “the logic of giving without reciprocation” instead of the “logic of power” or the “logic of the market” in the realm of economy and politics also. The Pope also observes that unless the “logic of giving without reciprocation” dominates human relations both poor and affluent societies will continue to grapple with increasingly serious and tragic issues, and this logic will apparently not prevail if people do not begin to believe again. The Encyclical Caritas in veritate assumes the form of a diagnosis that the modern world disregards. In the opinion of the Pope this lack of attention is not the fault of the Papacy, but rather of the world itself. Expressing this attitude, the Pope easily assumes a position which is comfortable from his point of view, and which cannot be refuted nor corroborated.